(x-y)^2-(m+n)^2=
(2a-3c)^2+(4b+5d)^2=

mamkin0poc mamkin0poc    1   22.02.2020 08:45    0

Ответы
Ekaterina152005 Ekaterina152005  11.10.2020 11:11

1)

Если нужно упростить:

\displaystyle \tt (x-y)^2-(m+n)^2=x^2-2xy+y^2-(m^2+2mn+n^2)=\boxed{\bold{x^2-2xy+y^2-m^2-2mn-n^2}}

Если нужно разложить на множители:

\displaystyle \tt (x-y)^2-(m+n)^2=(x-y-(m+n))(x-y+(m+n))=\boxed{\bold{(x-y-m-n)(x-y+m+n)}}

2)

\displaystyle \tt (2a-3c)^2+(4b+5d)^2=\boxed{\bold{4a^2-12ac+9c^2+16b^2+40bd+25d^2}}

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра